PENGARUH BRAND AWARENESS DAN BRAND IMAGE TERHADAP KEPUTUSAN INVESTASI DI BANK BRI - Anisah, Khoirul; Naila Najihah (Universitas Nias Raya, 2025)
This study aims to examine the influence of brand awareness and brand image on customers' investment decisions at BRI. Employing a quantitative approach, the research utilizes a random sampling technique with a total of 96 BRI customers as respondents. Data analysis was conducted using multiple linear regression tests through SPSS software. The results reveal that, simultaneously, brand awareness and brand image significantly influence customers’ investment decisions at BRI. High brand awareness helps customers recognize and recall BRI as a trusted investment institution, while a positive brand image enhances customer perception and trust in the quality and security of BRI’s investment products. Thus, both variables play a crucial role in shaping investment decisions. These findings highlight the importance of effective brand management strategies in increasing customer participation in investment products. Therefore, BRI is expected to continuously improve brand awareness and build a strong brand image to attract interest and reinforce customers’ investment decisions. This research is also expected to serve as a reference for developing more effective marketing strategies and innovative investment products in the future.